What determines students’ choices of elective modules? - Hedges, M; Pacheco, GA; Webber, D (University of Bristol, 2013)
Prior literature emphasises supply side issues concerning the modularisation of university programmes such as curricula issues and enhanced learning opportunities. Comparatively little is known about the demand side, such as why students choose specific modules. This article presents an investigation that was specifically designed to improve understanding of the factors that contribute to student module choices and draws on a large primary dataset comprised of students following a wide range of majors at a new university business school.
Keywords: Module choice; Curriculum design; Factor analysis